Palladium complex composites based on fullerene encapsulated in porous zinc porphyrin polymers. Issue 12 (2nd December 2021) - Shen, Tieyin; Chang, Zhaosen; Liu, Xin; Chen, Qi; Feng, Lijuan
Abstract: Porphyrins and fullerenes were suitable for the construction of multi-component reticular polymer owing to the interaction of their coordination. In this work, a novel organic porous polymer (PPZ/C60 ) composed of metalloporphyrin and fullerene was designed and constructed. Compared with the traditional sawtooth structure, a fullerene encapsulated in porous zinc porphyrin polymers (PPZ/C60 ) was fabricated by the combination of covalent and non-covalent interaction based on the "porphyrin-fullerene-porphyrin" self-assembly system. Subsequently, the composites containing palladium complexes (PPZ/C60 -Pd ) were further constructed by the coordination between Pd(PPh3 )4 and fullerene. Notably, the synthesized PPZ/C60 and PPZ/C60 -Pd displayed an ample and stable structure of channel, high specific surface area (516 m 2 g −1, 452 m 2 g −1 ) and uniform pore size (0.77 nm, 0.66 nm). Furthermore, the PPZ/C60 -Pd exhibited a significant catalytic performance in the deallylation reaction of 1, 4-diprop-2-enoxybenzene with different side-chain groups. This work not only expanded the structure of this material, but also provided more possibilities for the application of the PPZ/C60 -Pd . Graphical Abstract: UF0001